تطوير نظام إحصائي لتحقيق الاستثمار الأمثل لمعدات التشييد في سوريا - نجــا هــاني; مصطفـى ماهر; مكيـة سمــاح (Latakia University Journal -Engineering Sciences Series, 2019)
تعاني الشركات المحلية العاملة في مجال صناعة التشييد بشكل عام من خلل في إدارة معدات التشييد لديها ينتج عنه الاستثمار غير الاقتصادي لتلك المعدات؛ إذ تمتلئ المخازن بمعدات متوقفة عن العمل وتستنزف عمليات الإصلاح ميزانية تلك الشركات. تم اعتماد منهجية إحصائية تقوم على البيانات الميدانية التي تجمعها الشركات حول تكاليف المعدات وعدد ساعات تشغيلها بحيث يمكن لأية شركة محلية استخدامها انطلاقاً من بيانات معدات التشييد لديها من أجل إيجاد العلاقة بين عمر المعدة وكلفتها. وقد تم التوصل إلى المعادلات التراجعية التي تعبر عن العلاقة بين ساعات العمل المتراكمة ومعدل الكلفة التراكمي لمعدات التشييد في شركات القطاع العام عن طريق دراسة شريحة من هذه الشركات تضمنّت 181 معدة، وذلك بالاستفادة من الطرائق الإحصائية وخلصت الدراسة إلى الحصول على معادلات من الدرجة الثانية والدرجة الثالثة، ومن ثم تم ربطها مع موديل الكلفة التراكمي لاتخاذ القرارات الاقتصادية المناسبة لهذه المعدات. It has been observed that the local construction companies have a defect in their equipment management which causes an uneconomic investment in their equipment; the storages are full of broken equipment and repair operations consume the companies’ budgets. Statistical methodology has been based on the field data collected by the companies about the equipment cost and its operational use so that any local company can use this methodology to find the relation between the age of the equipment and its cost. The regressive equations have been found to express the relation between the cumulative hours of use and the cumulative cost for the construction equipment in companies of the public sector. Using the statistical methods, this has been done through a study of a cross-section of these companies including /181/ pieces of the construction equipment. Consequently, the second-order and third-order polynomial expressions were selected as the best. It was demonstrated how these expressions could be incorporated into the Cumulative Cost Model to identify the optimal economic decisions.